The regulatory mechanisms of proline and hydroxyproline metabolism: Recent advances in perspective - Phang, James M. (Frontiers in Oncology, 2023)
ABSTRACT For diverse human tumors, growth and metastasis are dependent on proline synthesis, but the mechanisms underlying this association are not clear. Proline incorporated into collagen is primarily synthesized from glutamine. Thus, rates of collagen synthesis are modulated by the enzymes of proline synthesis. On the other hand, the hydroxylation of collagen proline requires KG, ascorbate and ferrous iron, substrates necessary for the epigenetic demethylation of DNA and histones. The metabolic relationship of proline and hydroxyproline degradation are initiated by distinct dehydrogenases but the respective oxidized products, P5C and OH-P5C are substrates for P5C Reductase and P5C Dehydrogenase allowing for mutual competition. This provides a model by which proline synthesis in cancer plays a role in reprogramming gene expression. The metabolism of proline and hydroxyproline are also linked to the HIF response to hypoxia. Hypoxia increased the expression of ALDH18A1, which is the limiting step in proline and collagen synthesis. Hydroxyproline increases levels of HIF-1presumably by inhibiting its degradation. These new findings allow the suggestion that there is a regulatory axis from glutamine to proline and collagen synthesis, and the release of free hydroxyproline can feed back on the HIF pathway.